Computational evaluation of an optimum leading-edge slat deflection angle for dynamic stall control in a novel urban-scale vertical axis wind turbine for low wind speed operation. (August 2020) - Ullah, Tariq; Javed, Adeel; Abdullah, Ali; Ali, Majid; Uddin, Emad
Highlights: VAWT offer a potent solution for distributed urban-scale wind power generation. Leading-edge slat improves the dynamic stall performance of VAWT rotor. Leading-edge slat produces additional lift and protects main airfoil from stall. Advance slatted VAWT rotor reduces the vorticity field and blade-wake interaction. Abstract: This paper explores passive flow control via leading-edge (LE) slats to reduce the dynamic stall (DS) phenomenon and related blade-wake interaction in an H-Darrieus type vertical axis wind turbine (VAWT) operating under low wind speed conditions. A comprehensive 2D unsteady computational fluid dynamics (CFD) assessment has been carried out for the non-slatted baseline rotor and the advance slatted rotor (ASR) configurations. The unsteady Reynolds-averaged Navier-Stokes (URANS) approach with k-ω shear stress transport (SST) turbulence model and sliding mesh technique have been applied in Ansys Fluent. Optimum slat deflection angle δ has been evaluated using the single-blade oscillatory case with and without the LE slats. Results indicate a reduction in optimum δ from 16° at rated wind speed of 10 ms −1 to 12° for low wind speed operation at 5 ms −1 . A significant increase in the maximum coefficient of lift CL, max by approximately 32% and a delay in stall angle of attack αmax by 3° is obtained with ASR configuration compared to the baseline. Further assessment of the ASR configuration on the three-blade rotatory case demonstrates an increase in the power coefficient CP by approximately 15% at the rated tip-speed ratio λ compared to the baseline.